2019
DOI: 10.1002/jcb.28601
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 4‐miRNA signature as a potential prognostic biomarker for pancreatic adenocarcinoma

Abstract: An microRNA (miRNA) signature to predict the clinical outcome of pancreatic adenocarcinoma (PAAD) is still lacking. In the current study, we aimed at identifying and evaluating a prognostic miRNA signature for patients with PAAD. The miRNA expression profile and the clinical information regarding patients with PAAD were recruited from The Cancer Genome Atlas database. Differentially expressed miRNAs were identified between normal and tumor samples. By means of survival analysis, a 4‐miRNA signature for predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…proved to be a potential prognostic biomarker for some cancers in some studies [21,22]. Besides, miR-424 can suppress the metastasis and invasion of HCC [23].…”
Section: Plos Onementioning
confidence: 99%
“…proved to be a potential prognostic biomarker for some cancers in some studies [21,22]. Besides, miR-424 can suppress the metastasis and invasion of HCC [23].…”
Section: Plos Onementioning
confidence: 99%
“…Moreover, GLI1 co-expressed and DEGs between tumor samples and normal tissues were both largely enriched in the PI3K-Akt pathway in STAD (Yu et al, 2018;Li et al, 2019). In PAAD, 4-miRNA as independent prognostic factor was found to be related to the PI3K-Akt signaling pathway (Wang et al, 2019). Growing evidence revealed that the ErbB and PI3K-Akt signaling pathways play vital roles in colorectal cancer by regulating microRNA, lncRNA, mRNA, etc.…”
Section: Discussionmentioning
confidence: 95%
“…We have analyzed the performance of our final prognostic model in comparison with the previously identified prognostic markers obtained from several published studies. We observed that our splice event based seven gene prognostic model (HR = 9.13; P-value = 6.42e-10, Concordance = 0.7; and 5yr AUC = 0.93) outperformed the existing PAAD specific prognostic markers such as five miRNAs (HR = 0.13; P < 0.001) (Liang et al, 2018) and four miRNAs based prognostic models (HR= 2.8; P < 0.001; 2yr AUC = 0.79) (Wang, Deng, & Ma, 2019), 20 gene-based prognostic signature (HR = 2.01; P = 0.007) (Canlı et al, 2020), three lncRNA signature (P < 0.001; AUC = 0.72) (Shi et al, 2018), 29 gene-based ceRNA signature (HR = 1.66; P < 1.0e-04) (Zhao & Liu, 2017); 9 gene prognostic signature (P < 0.0001; 1yr AUC = 0.70) (Wu, Li, Zhang, Liu, & Zhao, 2019), and 7 gene-based AS event prognostic signature (AUC = 0.89) (Yu et al, 2019). Our splice-event based prognostic marker also outperformed an exisiting study in terms of HR and AUC that evaluates the risk assessment capability of PAAD related AS events (Xu, Pan, Ding, & Pan, 2020).…”
Section: Improved Performance Over Existing Paad Prognostic Signaturesmentioning
confidence: 91%